Langerhans cell histiocytosis is a neoplasm and consequently its recurrence is a relapse: In memory of Bob Arceci. Issue 10 (17th June 2016) - Egeler, R. Maarten; Katewa, Satyendra; Leenen, Pieter J.M.; Beverley, Peter; Collin, Matthew; Ginhoux, Florent; Arceci, Robert J.; Rollins, Barrett J.; ,
Abstract: Langerhans cell histiocytosis (LCH) remains a poorly understood disorder with heterogeneous clinical presentations characterized by focal or disseminated lesions that contain excessive CD1a+ langerin+ cells with dendritic cell features known as "LCH cells." Two of the major questions investigated over the past century have been (i) the origin of LCH cells and (ii) whether LCH is primarily an immune dysregulatory disorder or a neoplasm. Current opinion is that LCH cells are likely to arise from hematopoietic precursor cells, although the stage of derailment and site of transformation remain unclear and may vary in patients with different extent of disease. Over the years, evidence has provided the view that LCH is a neoplasm. The demonstration of clonality of LCH cells, insufficient evidence alone for neoplasia, is now bolstered by finding driver somatic mutations in BRAF in up to 55% of patients with LCH, and activation of the RAS‐RAF‐MEK‐ERK (where MEK and ERK are mitogen‐activated protein kinase and extracellular signal‐regulated kinase, respectively) pathway in nearly 100% of patients with LCH. Herein, we review the evidence that recurrent genetic abnormalities characterized by activating oncogenic mutations should satisfy prerequisites for LCH to be called a neoplasm. As a consequence, recurrent episodes of LCH should be considered relapsed disease rather than disease reactivation. Mapping the complete genetic landscape of this intriguing disease will provide additional support for the conclusion that LCH is a neoplasm and is likely to provide more potential opportunities for molecularly targeted therapies.